Interaction of LARP4 to filamin A mechanosensing domain regulates cell migrations - Mao, Zhenfeng; Nakamura, Fumihiko (Frontiers in Cell and Developmental Biology, 2023)
Filamin A (FLNA) is an actin cross-linking protein that mediates mechanotransduction. Force-dependent conformational changes of FLNA molecule expose cryptic binding site of FLNA, allowing interaction with partners such as integrin, smoothelin, and fimbacin. Here, we identified La-related protein 4 (LARP4) as a new FLNA mechanobinding partner. LARP4 specifically interacts with the cleft formed by C and D strands of immunoglobulin-like repeat 21 (R21) which is blocked by A strand of R20 without force. We validated the interaction between LARP4 and FLNA R21 both in vivo and in vitro. We also determined the critical amino acid that is responsible for the interaction and generated the non-FLNA-binding mutant LARP4 (F277A in human: F273A in mouse Larp4) that disrupts the interaction. Fluorescence recovery after photobleaching (FRAP) of GFP-labeled LARP4 in living cells demonstrated that mutant LARP4 diffuses faster than WT LARP4. Proximity ligation assay (PLA) also confirmed their interaction and disruption of actin polymerization diminishes the interaction. Data mining of RNAseq analysis of LARP4 knockdown (KD) HEK293T cells suggested that LARP4 is involved in morphogenesis and cell motility. Consistent with this prediction, we found that KD of LARP4 increases cell migration speed and expression of the F277A mutant LARP4 in LARP4-KD cells also leads to a higher cell migration speed compared to WT LARP4. These results demonstrated that the LARP4 interaction with FLNA regulates cell migration.